Literature Review : Perbandingan Nilai PetCO2 dan PaCO2 Pada Pasien Kritis Terpasang Ventilasi Mekanik - Gunarti, Tri; Sukartini, Tintin; Mirzanah, Syafaatun (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Monitoring carbon dioxide in patients on mechanical ventilation is crucial for critical care nurses. Monitoring the value of arterial carbon dioxide pressure involves invasive arterial blood gas analysis. Monitoring end-tidal carbon dioxide pressure using capnography is a non-invasive method. This study aims to compare end-tidal carbon dioxide values with arterial carbon dioxide pressure in mechanically ventilated patients. The research design is a literature review. Searches were conducted through Scopus, ScienceDirect, ProQuest, and PubMed from 2018 to 2023. The Preferred Reporting Items for Systematic Review and Meta-Analyses flowchart method was used to select articles. The Critical Appraisal Skills Programme was used to assess article quality. Out of 79 articles, nine articles met the criteria. The procedures for collecting end-tidal carbon dioxide pressure and arterial carbon dioxide pressure data varied in terms of instrument types used and the subjects studied. There was no significant difference in carbon dioxide values between the end-tidal carbon dioxide and arterial carbon dioxide pressure methods. The agreement in comparing carbon dioxide values was acceptable. Measuring end-tidal carbon dioxide pressure has the potential to monitor mechanically ventilated patients, reducing the need for invasive monitoring, high costs, and repetitive arterial blood gas analysis.